PROMOTING PARTICIPATION IN LOCAL POLITICS FOR PEOPLE IN THE SIWICHAI SUBDISTRICT A DMINISTRATIVEORGANIZATION, PHUNPHIN DISTRICT, SURAT THANI PROVINCE - Bumsamran, Somchai; Nuthongkaew, Kantaphon (Journal of MCU Nakhondhat, 2024)
The objectives of this research are 1) To study the level of promoting participation in local politics; To the people of Sriwichai Subdistrict Administrative Organization, Phunphin District, Surat Thani Province 2) To study ways to promote participation in local politics for the people of Sriwichai Subdistrict, Phunphin District, Surat Thani Province Use a mixed methods research method. Quantitative research methods collected data from people living in the area of Sriwichai Subdistrict Administrative Organization, Phunphin District, Surat Thani Province. The sample group consisted of 333 people. Statistics used included frequency, percentage, mean, and standard deviation. Qualitative research Use the in-depth interview method. from 5 key informants and content analysis The research results found that 1) Promoting participation in local politics of the Siwichai Subdistrict Administrative Organization, Phunphin District, Surat Thani Province, in all 4 areas, is at a high level. When considering each aspect by ordering the average from highest to lowest, it was found that the collaborative thinking aspect ( = 4.28, S.D. = 0.66) had the highest mean, followed by the planning operations aspect ( = 4.17, S.D. = 0.55.) As for the decision-making aspect ( = 3.99, S.D. = 0.62), it has the lowest average. 2) Guidelines for promoting participation in local politics of the Siwichai Subdistrict Administrative Organization, Phunphin District, Surat Thani Province, of the people through a format called CDPE. MODEL, that is, 1) C means Consultation (consultation is thinking together Participation in thinking and giving opinions to Subdistrict Administrative Organization in implementing the project according to the community development plan Participate in supporting and helping operations), 2) D means Decide (decision making), 3) P means Plan (planning) 4) E means Evaluate (evaluation is checking)